How Does the Coal Stock Market, Carbon Market and Coal Price Co-movement with Each other in China: A Co-movement Matrix Transmission Network Perspective. (May 2017) - Li, Huajiao; An, Haizhong
Abstract: As the global warm problem becomes more and more serious, many countries try hard to develop a low carbon economy and build a low carbon society. Along with low carbon development, the carbon market has grown up around the world. Meanwhile, as the key body of the coal industry, coal listed companies suffered a lot due to the low carbon development. As many countries, China also pay lots of effort to cut down the consumption of coal products, so as to realize the restructuring of energy industry. In this paper, we try to find our whether the China's coal stock market, carbon market and coal price co-movement with each other in a certain way. First, we defined the co-movement matrix of the coal stock market, carbon market and coal price (three indices for short) in each trading day which can show the co-movement patterns between any of the two indices. Then, based on complex network method, we took the co-movement matrices as nodes, the time adjacent relations as edges to construct the co-movement matrix transmission network, and the role of each co-movement matrix, the relations between any of the two co-movement matrices, as well as the important group of the co-movement matrix transmission network were analyzed based on different topological features. Finally, based on the results, we analyzed the co-movement relations of carbon-related markets. The method proposed in this manuscript is helpful for the researchers to find out how the low carbon development affects different markets, and it is also helpful for the investors to analyze what the co-movement patterns of different markets in a holistic perspective.